Characterization of Dendritic Cell and Regulatory T Cell Functions against Mycobacterium tuberculosis Infection. (23rd May 2013) - Morris, Devin; Gonzalez, Brenda; Khurasany, Melissa; Kassissa, Christine; Luong, Jennifer; Kasko, Sarah; Pandya, Shalin; Chu, Michael; Chi, Po-Ting; Bui, Steven; Guerra, Carlos; Chan, John; et al.
Abstract : Glutathione (GSH) is a tripeptide that regulates intracellular redox and other vital aspects of cellular functions. GSH plays a major role in enhancing the immune system. Dendritic cells (DCs) are potent antigen presenting cells that participate in both innate and acquired immune responses against microbial infections. Regulatory T cells (Tregs) play a significant role in immune homeostasis. In this study, we investigated the effects of GSH in enhancing the innate and adaptive immune functions of DCs against Mycobacterium tuberculosis ( M. tb ) infection. We also characterized the functions of the sub-populations of CD4+T cells such as Tregs and non-Tregs in modulating the ability of monocytes to control the intracellular M. tb infection. Our results indicate that GSH by its direct antimycobacterial activity inhibits the growth of intracellular M. tb inside DCs. GSH also increases the expressions of costimulatory molecules such as HLA-DR, CD80 and CD86 on the cell surface of DCs. Furthermore, GSH-enhanced DCs induced a higher level of T-cell proliferation. We also observed that enhancing the levels of GSH in Tregs resulted in downregulation in the levels of IL-10 and TGF- β and reduction in the fold growth of M. tb inside monocytes. Our studies demonstrate novel regulatory mechanisms that favor both innate and adaptive control of M. tb infection.